Penerapan K3 pada Pelaksanaan Proyek Pembangunan Gedung Olahraga (GOR) ASR Center Kota Kendari - Sakti, Putra; Pratama, Ardi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Occupational safety and health (K3) is a program created for workers or laborers or companies as a form of prevention of work accidents that may occur to workers in the work environment. The purpose of this study was to determine the implementation and supervision of K3 in the implementation of the ASR Center sports building (GOR) construction project in Kendari City. The study was conducted using a descriptive method with quantitative analysis. While data collection was carried out through field observations and distributing questionnaires to staff and workers. The results of the achievement of the implementation of occupational safety and health (K3) on the grandstand ladder work reached 82%, column repair 84%, steel frame installation 79% and roof installation 84%. From the four applications of occupational safety and health (K3), an average percentage of 82.25% was obtained, the four jobs were categorized as "very good". PT. Aji Konstruksi Utama in carrying out safety patrols or direct supervision is carried out by Health, Safety, Environment (HSE) to supervise the work.